Developing Description Writing Skills through Comic-based Story - Veronika Unun Pratiwi; Farida Nugrahani; Suhailee Sohnui; Maram Taher (Journal of Innovation in Educational and Cultural Research, 2024)
Writing descriptions is one of several forms of writing skills that express students' impressions, perceptions, and feelings. This study aims to create appropriate teaching resources for use in learning to write descriptions in the Indonesian language subject. The product in this study is a learning resource in the form of the comic book ‘Kisah Teladan bersama Punakawan’ for fourth-grade students at a state elementary school in Central Java. This is a modified Research and Development (RD) study from Borg and Gall's (1983) development mode designed with a qualitative research method. Based on the feasibility validation of assessment learning resources from six validators, material experts, language experts, and media experts, the book was suitable for improving students' writing skills in the description text. It could be used as an additional learning resource for Indonesian subjects to improve students' skills in writing description text inspired by the Punakawan wayang stories.